Músicos da noite de Fortaleza nadDécada de 1990: formação de um habitus musical - Monteiro, Sílvio Mauro Modesto (2018)
This work investigates and describes, using Pierre Bourdieu's field and habitus concepts, formation and trajectory of a generation of musicians, singers and composers, who performed at night in bars and restaurants of Fortaleza between the middle of the 1990s and the beginning of the 2000s. It refers to the albums “Som da noite (Sound of the Night) volume 1”, released in 2002, and “Som da noite (Sound of the Night) volume 2”, released in 2003. These referred albums are used because they are considered two milestones of consolidation for the trajectories of the artists as they helped to make know their work as professionals outside the night music scene and served as a way to legitimize their careers both among their colleagues and the public. The research involves the following main aspects: study of formation process to the night musicians (and, consequently, their musical habitus), identification of their trajectories as professionals and consolidation at the environment in which they acted. A search was made by recognition of common points among musicians, both in their formation process and trajectory. For this, the methodological procedures of the qualitative research and Pierre Bourdieu´s praxeology was used. The work looked for answers to the following questions: what is the formation process of musicians in this musical field? How was this field constituted? What is the cultural capital acquired at the formation process of these musicians? How did the process of legitimation and recognition take place in the musical field? What were their instances of consecration? These questions turn out to be a central query: how did these agents become what they are, i.e., how did they become night musicians?